Menstrual disorders associated with thyroid dysfunction - R., Ramya M.; Parvathavarthini, .; Savery, Darshan; Sankareswari, R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Present study was done to evaluate the thyroid function in patients presenting with varying menstrual patterns of reproductive age group from 15 to 45 years of age. Methods: This prospective study was carried out in obstetrics and gynecology Department of Sri Venkateshwaraa Medical College, Pondicherry, India on 155 women, clinically given the provisional diagnosis of dysfunctional uterine bleeding (DUB). All these patients were investigated for T3, T4, TSH (Thyroid stimulating hormone) levels and grouped according to that. Results: Among the 155 women (58.7%) were normal thyroid function, (41.3%) had hypothyroid and (1.3%) had subclinical hypothyroidism. Conclusions: There is a high prevalence of thyroid disorders in cases which are clinically diagnosed as DUB. Evaluating for thyroid and treating it medically which was most accurate and cost effective and unnecessary surgery was avoided. Hence the thyroid function evaluation should be mandatory in cases of DUB to detect thyroid dysfunction and these cases should be referred to physician for further medical treatment.